수술 후 유착성 소장폐쇄증에서의 조영제(UltravistⓇ) 검사의 유용성 - 조홍진(Hong Jin Cho); 조민식(Min Sik Cho); 김도균(Do Gyun Kim); 윤대선(Dae Sun Youn); 김강성(Kang Sung Kim); 박배근(Bae Geun Park); 김곤홍(Gon Hong Kim); 김우길(Woo Gil Kim) (Annals of surgical treatment and research, 2004)
Purpose: To determine whether Ultravist test can enable the surgeon to differentiate complete from partial small bowel obstruction in patients with adhesive small bowel obstruction and whether partial small bowel obstruction can be treated nonoperatively. Methods: Ninety-two patients who had postoperative small bowel obstructions without any toxic signs underwent Ultravist test. Ultravist (40 ml) mixed with 40 ml of distilled water was administrated either orally or via nasogastric tube to each patient. Serial plain abdominal radiographs were taken 4, 6, and 8 hours later. Results: A total of 58 patients (63%) whose contrast medium reached the colon within the first 8 hours were considered to have partial obstruction (test positive) and were successfully treated with intravenous hydration and nasogastric decompression. The remaining 34 patients (36.9%), in whom the contrast medium failed to reach the colon within the first 8 hours (test negative), were regarded as having complete obstruction. Twenty-three of those patients (67.6%) underwent surgery and the other 11 (32.4%) received conservative treatment. Adhesion bands with complete bowel obstruction were observed in all 23 surgical patients during laparotomy. All the patients with partial bowel obstruction were treated successfully with nonoperative methods. Positive Ultravist test as an indicator for nonoperative treatment had a sensitivity of 84.5%, a specificity of 100%, an accuracy of 88% and a false negative rate of 12%. Conclusion: Ultravist can be used to differentiate partial from complete intestinal obstruction. All patients with evidence of Ultravist reaching the colon within 8 hours were treated successfully with non-operative methods. KCI Citation Count: 0